THE EFFECT OF FIRM SIZE, GROSS PROFIT MARGIN AND INSTITUTIONAL OWNERSHIP ON DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) - Pipit Rosita Andarsari (Jurnal Apresiasi Ekonomi, 2019)
The objective of this research is to analyze influence of Size, Gross Profit Margin (GPM) and Institusional Ownership to Corporate Social Responsibility (CSR) Disclosure. Sample of this research are annual report for manufacture companies that listed in Indonesia Stock Exchange (BEI) in 2014-2016. Sample were selected using purposive sampling method and 11 sample were able to fullfill the criteria used as sample. This research uses multiple regression data analysis techniques . The result of the research showns that size and gross profit margin has positive effect on the corporate social responsibility , meanwhile Institutional ownership has negative effect on the corporate social responsibility. Keywords: Size, Gross Profit Margin, Institutional Ownership, Corporate Social Responsibility